2008
DOI: 10.1080/17470910701577020
|View full text |Cite
|
Sign up to set email alerts
|

Levels of emotional awareness and autism: An fMRI study

Abstract: Autism is associated with an inability to identify and distinguish one's own feelings. We assessed this inability using alexithymia and empathy questionnaires, and used fMRI to investigate brain activity while introspecting on emotion. Individuals with high functioning autism/Asperger syndrome (HFA/AS) were compared with matched controls. Participants rated stimuli from the International Affective Picture System twice, once according to the degree of un/pleasantness that the pictures induced, and once accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
317
1
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 401 publications
(352 citation statements)
references
References 39 publications
25
317
1
3
Order By: Relevance
“…In a break with previous research, however, we claim that there is a second distinct influence within these data: an inability to attend to emotional facial features in an optimal manner that is associated with alexithymia. Such a distinction supports the independence of autism and alexithymia reported elsewhere (Bird et al 2010;Hill et al 2004;Silani et al 2008), although the reason for the increased prevalence of alexithymia in individuals with autism is still unknown.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In a break with previous research, however, we claim that there is a second distinct influence within these data: an inability to attend to emotional facial features in an optimal manner that is associated with alexithymia. Such a distinction supports the independence of autism and alexithymia reported elsewhere (Bird et al 2010;Hill et al 2004;Silani et al 2008), although the reason for the increased prevalence of alexithymia in individuals with autism is still unknown.…”
Section: Discussionsupporting
confidence: 85%
“…However, more research is needed on the important question of whether alexithymia in individuals with ASC is due to the same cause, and is manifested similarly, as in individuals without ASC. Notwithstanding these limitations, these results and others (Bird et al 2010;Silani et al 2008) suggest that the presence of alexithymia defines a subgroup of individuals with an autism spectrum disorder who exhibit emotional impairments related both to the self and the other in addition to the characteristic social impairments.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Parent, but not self‐reports of irritability and anxiety were positively correlated, which may be due to introspection difficulties or alexithymia, a condition characterized by difficulties in identifying and describing emotions (e.g., Silani et al., 2008). Future studies should examine this possibility, since introspection difficulties and alexithymia were not measured in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the ASD pattern of attention allocation was not related to the severity of their autistic symptoms (ADOS scores), alexithymia scores were found to be negatively correlated with the number of fixations to the eye region (relative to the mouth region) (see also Lombardo et al, 2007). At the cerebral level, this issue is well illustrated in a study which investigated the neural correlates of empathy for pain in adults with ASD and healthy controls: Bird et al (2010) not only showed that, in both groups, the higher the level of alexithymia the lower the empathy-related activity in the insula when the partner received pain, but also that there were no group differences in brain activity when alexithymia scores were entered as a covariate (see also Silani et al 2008). Thus, extending our knowledge of socio-affective abnormalities such as alexithymia, as well as anhedonia (i.e., the inability to experience pleasure) in ASD could not only explain previously inconsistent results in our understanding of ASD (Bird et al, 2011; see also Bernhardt and Singer 2012), but also help to tailor therapeutic interventions for this group.…”
Section: Introductionmentioning
confidence: 90%